Efficacy of medical grade honey in the management of canine otitis externa – a pilot study. Issue 2 (1st March 2016) - Maruhashi, Emi; Braz, Berta São; Nunes, Telmo; Pomba, Constança; Belas, Adriana; Duarte‐Correia, José Henrique; Lourenço, Ana Mafalda
Abstract : Background: The high prevalence of antimicrobial resistance within otic pathogens has created a need for alternative therapies of otitis externa (OE). Evidence suggests that medical grade honey (MGH) may be effective against drug‐resistant pathogens. Hypothesis/Objectives: The efficacy of a commercial MGH compound was assessed in an open clinical trial. We hypothesized that it would be an effective alternative to conventional treatments. Animals: Client‐owned dogs ( n  = 15) with a confirmed diagnosis of infectious OE were enrolled in this pilot study. Methods: Dogs were prescribed MGH (1 mL daily per ear) until cure was achieved or for a maximum of 21 d. Evaluation was based on weekly clinical scores, cytological progression and owner assessments of pruritus. Swab samples were submitted for culture and susceptibility testing. MGH was tested for biocidal activity against the bacterial isolates. Results: Medical grade honey promoted rapid clinical progress, with 70% of dogs achieving clinical cure between days 7 and 14 and over 90% having resolved by Day 21. There was a decrease in clinical scores throughout the duration of the trial ( P  <   0.001) and owner‐assessed pruritus also decreased significantly ( P  <   0.05). In vitro assays of the biocidal activity of MGH showed activity against all bacterial isolates, including meticillin‐resistant strains of Staphylococcus pseudintermedius (MRSP) and other species of drug‐resistant bacteria. Conclusion and clinical importance: Medical grade honey was successful in both clinical and laboratory settings, thus demonstrating its potential of becoming an alternative treatment for canine OE. Abstract : Background – The high prevalence of antimicrobial resistance within otic pathogens has created a need for alternative therapies of otitis externa. Evidence suggests that medical grade honey (MGH) may be effective against drug‐resistant pathogens.Hypothesis/Objectives – The efficacy of a commercial MGH compound was assessed in an open clinical trial. We hypothesized that it would be an effective alternative to conventional treatments.Conclusion and clinical importance – Medical grade honey was successful in both clinical and laboratory settings, thus demonstrating its potential of becoming an alternative treatment for canine otitis externa.